1988
DOI: 10.1002/cne.902730304
|View full text |Cite
|
Sign up to set email alerts
|

Development of β1 and β2 adrenergic receptors in baboon brain: An autoradiographic study using [125I]iodocyanopindolol

Abstract: [125I]iodocyanopindolol (ICYP) autoradiography was used to investigate the temporal development and distribution of beta 1 and beta 2 receptors in brains of baboons at ages embryonic day 100 (E100), full-term gestation (El80), and 3 years. In all brain regions examined, with the exception of the hippocampus, binding to beta 1 receptors exceeded that to beta 2 receptors. The highest densities of beta 1 receptors were found in the caudate nucleus, putamen, globus pallidus, substantia nigra, and cerebral cortex; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 48 publications
2
8
0
2
Order By: Relevance
“…A few available studies of the striatum in baboons show prenatal and/or postnatal changes in adrenergic, cholinergic, and dopaminergic ligand binding sites by autoradiography (Slesinger et al, 1988; Lowenstein et al, 1989) as well as sodium-dependent high affinity choline uptake binding sites (Lowenstein et al, 1987). However the normal spatiotemporal development of connectively, cell adhesion molecules, synapses, neurotransmitters, receptor proteins, and signal transduction molecules in the striatum of non-human primates is mostly unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A few available studies of the striatum in baboons show prenatal and/or postnatal changes in adrenergic, cholinergic, and dopaminergic ligand binding sites by autoradiography (Slesinger et al, 1988; Lowenstein et al, 1989) as well as sodium-dependent high affinity choline uptake binding sites (Lowenstein et al, 1987). However the normal spatiotemporal development of connectively, cell adhesion molecules, synapses, neurotransmitters, receptor proteins, and signal transduction molecules in the striatum of non-human primates is mostly unknown.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with previous studies in the avian brain, where ICYP binding attributable to b 2 -ARs is higher in the chick and pigeon mesopallium and hippocampus as compared to b 1 -AR binding (FernandezLopez et al, 1997). However, in mammalian species (baboon, rat, guinea-pig), b 1 -AR binding was higher in all brain regions, apart from the hippocampus, where b 2 -AR binding was higher in baboons (Slesinger et al, 1988) but similar levels in rat and guinea-pig hippocampus (Booze et al, 1989). Another study in rat hippocampus showed higher b 1 -AR populations as compared to b 2 -ARs (Rainbow et al, 1984).…”
Section: Role Of Hippocampal B 1 -Ars In Memory Formationmentioning
confidence: 95%
“…Thus, the hypothesis that disturbances in the expression of p1 receptors predominantly contribute to neuropsychiatric illness is largely based on studies of beta-receptor regulation in the rat. It is known that the distribution of P-receptors varies significantly between the rat and other species, such as the guinea pig, baboon, and human (Booze et al, 1989;De Paermentier et al, 1989;Pazos et al, 1985;Reznikoff et al, 1986;Shimohama et al, 1987;Slesinger et al, 1988). Thus, it is possible that the regulation of P-receptors may also vary between species.…”
Section: Introductionmentioning
confidence: 99%